Tingkat Kesehatan Bank Umum Syariah (Studi Kasus Bank Swasta Nasional) - musadat, Irfan Achmad (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
This research aims to analyze the health level of Sharia commercial banks in Indonesia. The research method utilizes financial ratio indicators established by Bank Indonesia Regulations (PBI No. 9/1/PBI/2007) and Financial Services Authority Regulations (Number 8/POJK.03/2014). Various indicators of the health level of Islamic banks are analyzed, including financial ratios such as CAR (Capital Adequacy Ratio), ROA (Return on Assets), NPM (Net Profit Margin), BOPO (Operating Costs to Operating Income), NPF net (Non-Performing Financing net), and FDR (Financing to Deposit Ratio). This research focuses on evaluating the results of bank health level assessments as a benchmark for Sharia bank performance during the 2020 COVID-19 pandemic. The research object involves Sharia commercial banks in Indonesia. The required data is obtained from Islamic bank financial reports, and data analysis is carried out using the CAMEL method established by Bank Indonesia. It is hoped that the results of this research can provide important information for economic actors to understand and evaluate the health level of Sharia commercial banks in Indonesia during the 2020 COVID-19 pandemic. This information can be the basis for better economic decisions amidst uncertain economic conditions.